Theaflavins enhances laying hen production performance and egg antioxidant capacity via improving antioxidant status and regulating lipid metabolism - Zhou, Ling; Zhao, Pinyao; Zhang, Jinwei; Zhong, Jie; Rao, Yulin; Tang, Jia; Jiang, Longsheng; Chen, Fen; Chen, Lijuan; Zhang, Keying; Ouyang, Weimin; Peng, Jialong (Frontiers in Veterinary Science, 2025)
IntroductionTheaflavins (TF), natural compounds extracted from black tea, demonstrate various beneficial functions including antioxidant properties and lipid metabolism regulation. However, their effects on laying hens remained unclear. This study investigated the effects of different TF levels on production performance, egg quality, antioxidant capacity, lipid metabolism in laying hens, and egg antioxidant capacity.MethodsA total of 512 twenty-nine-week-old Lohmann commercial laying hens were randomly divided into four dietary treatments (0, 250, 500, or 1000 mg/kg TF) in a completely randomized design. Each treatment consisted of eight replicates of 16 birds, and the experiment lasted for 8 weeks. Data were analyzed using one-way analysis of variance (ANOVA) followed by Duncan’s multiple range test, with quadratic polynomial contrasts applied to evaluate dose-response relationships.ResultsResults showed that TF supplementation quadratically increased (p < 0.05) egg production, egg yolk color, serum total antioxidant capacity (T-AOC), hepatic T-AOC, uterine T-AOC, hepatic superoxide dismutase activity, serum total cholesterol (TC), hepatic TC, hepatic triglycerides, and the expression of antioxidant-related and lipid metabolism-related genes. It also enhanced the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capacity, T-AOC, tyrosine, and tryptophan levels in egg yolks. TF supplementation significantly decreased (p < 0.05) malondialdehyde (MDA) levels in serum, liver, ovaries, and egg yolks.ConclusionThese findings suggest that TF improves laying performance by enhancing antioxidant capacity and regulating lipid metabolism, while simultaneously boosting egg antioxidant potential. Based on the quadratic regression analysis, the optimal TF supplementation level was determined to be 500 mg/kg.